Resilience, Psychological Well-Being, and Employee Job Stress - Puspaningrum, Puspaningrum; Matulessy, Andik; Rini, Rr. Amanda Pasca (International Journal of Social and Management Studies, 2023)
This study aims to determine the relationship between resilience and employee welfare with work stress on employees. The subjects in this study were 150 employees using simple random sampling technique. The method in this study used multiple regression analysis with analytical techniques using SPSS version 26 for windows. Based on the results of the data analysis conducted, it is known that 1) Simultaneously, resilience and psychological well-being are proven to have a significant relationship with work stress. These two variables together have a contribution of 96.4% in reducing work stress levels; 2) Resilience is proven to have a negative and significant relationship with work stress; 3) Psychological well-being is proven to have a negative and significant relationship with work stress